Phenotypic diversity of colored phytochemicals in sorghum accessions with various pericarp pigments - Davis, Haley N. (Kansas State University, 2018)
Sorghum is a versatile grain that is generally consumed in Asian and African countries but is gaining interest in the United States due to its gluten-free and bioactive compound enriched health benefits. There are many varieties of sorghum that come in a wide range of colors. These genetic factor-depended phenotypic colors are contributed by various phytochemical pigments that reside within different components of the sorghum kernel, especially in the pericarp and endosperm. Various pericarp pigments are reflective of the certain phytochemical levels which may include anthocyanins, carotenoids, and condensed tannins. This article reviews recent studies on the association of pericarp pigments in various sorghum accessions with anthocyanins and carotenoids, respectively. It covers aspects of the potential health benefits of these colored dietary constituents. However, further investigations are warranted to clarify the diversity of these bioactive constituent interactions with genetic and environmental factors. How these phytochemicals correlate to the sorghum pericarp pigments could be important in future use of sorghum as a functional food with potential health benefits.
Keywords: Sorghum; Phytochemicals; Anthocyanins; Carotenoids